The Island Treasure - Hutcheson, John C. (John Conroy); Stacey, W. S. (Walter S.), 1846-1929 (Salt Lake City, UT : Project Gutenberg, 2007)
"The Island Treasure, or The Black Man's Ghost" by John C. Hutcheson is a novel likely written in the late 19th century. The story is narrated from the perspective of a young cabin-boy who has run away to sea, involving themes of adventure and treasure hunting. The backdrop includes a nasty captain and a shipwreck that leads to treasure on a mysterious island. At the start of the novel, readers are introduced to the tumultuous life aboard the ship "Denver City" under the command of the irritable Captain Snaggs. As the ship battles unfavorable weather, the crew's struggles are vividly depicted, highlighting their fears and reluctance to heed their captain's harsh orders. The narrative establishes the tension between the crew and their captain, the diverse accents and backgrounds of the ship's personnel, as well as hints of impending adventure and danger, especially after the crew encounters a tsunami that wrecks the ship on Abingdon Island. The young cabin-boy$1 (Bs perspective provides a unique lens through which these events unfold, setting the stage for the mystery surrounding both the treasure and the titular ghost. (This is an automatically generated summary.)s
Release date is 2007-10-21
Produced by Nick Hodson of London, England
Keywords: Sea stories; Treasure troves -- Fiction